Inflammatory potential of monospecies biofilm matrix components. (5th March 2019) - Ramirez, T.; Shrestha, A.; Kishen, A.
Abstract: Aim: To assess the inflammatory potential of biofilm matrix constituents of Enterococcus faecalis and Pseudomonas aeruginosa monospecies biofilms on macrophages. Methodology: In vitro biofilms of E. faecalis and P. aeruginosa were grown (7 days) in aerobic and anaerobic conditions. The biofilm matrix components: exopolysaccharides (EPS) and extracellular DNA (eDNA) were extracted and quantified. The inflammatory potential of EPS and eDNA was assessed on macrophage cell lines (RAW 267.4) using nitric oxide (NO), and enzyme‐linked immunosorbent assay for tumour necrosis factor (TNF‐α) and interleukin‐6 (IL‐6) expressions. LPS from P. aeruginosa and planktonic bacteria were positive controls. One‐way analysis of variance and the Tukey post hoc test were used for statistical analysis. Results: Extracted EPS from both biofilm strains was associated with higher levels than eDNA in both growth conditions ( P < 0.05). The biofilm components had less inflammatory potential compared to planktonic bacteria and LPS. EPS produced higher levels of inflammatory response compared to eDNA for both strains ( P < 0.05). IL‐6 and TNF‐α, and NO expression showed no difference for E. faecalis EPS ( P ≥ 0.05). In contrast, P. aeruginosa EPS and eDNA had significant levels of IL‐6 compared to TNF‐α and NO ( P < 0.05). Conclusions: Monospecies biofilm matrix EPS and eDNA from the bacterial strains tested had the ability to induce a low‐grade inflammatory response when compared to planktonic bacteria and LPS. This study highlights the potential of biofilm matrix/components, devoid of bacteria to induce low‐grade chronic inflammation.